Tribunal penal internacional e o impacto com a ordem jurídica interna. - Soares Neto, Edigardo Ferreira (2015)
In this dissertation, it will be made an approach to the International Criminal Court (ICC) rules in comparison with those of the Brazilian legal system, what coincide, making a check analysis of possible antinomies between internal standard and internalized. In this north, will be carried out an assessment of International Courts historical evolution that existed and the Court of Rome predecessors forms, in addition to the perception of data relating to its creation and accession of Brazil for their rules. In sequence, the features Court are related and, in this line, individual criminal responsibility, own this approach, in addition to the reflection on the concept of the Statute Member States sovereignty. Then the study is concentrated on the examination of international criminal law in comparison with the international criminal law, where international cooperation is addressed, in addition to the core crimes and criminal principles common to the internal order and external, all under the rules paradigm for the protection of international human rights. Finally, it will be checked the apparent shocks between constitutional rules and the Rome Statute, a verification of compatibility, a control of all juridical convention on domestic law impact and effect.